Everyday life : a poetics of vernacular practices - Abrahams, Roger D. (University of Pennsylvania Press, 2005)
"Everyday Life explores the entire range of social gatherings, from chance encounters and casual conversations to well-rehearsed performances in theaters and stadiums. Roger D. Abrahams ties the everyday to those more intense experiences of playful celebration and serious power displays and shows how these seemingly disparate entities are cut from the same cloth of human communication."--Jacket